Taxonomic utility of niche models in validating species concepts: A case study in Anthophora (Heliophila) (Hymenoptera: Apidae) - Orr, Michael C.; Koch, Jonathan B.; Griswold, Terry L.; Pitts, James P. (Zootaxa, 2014)
Taxonomy has far-reaching effects throughout biology, and incorrect taxonomy can be detrimental in many ways. Polymorphic species complexes, many of which exist in the bee genus Anthophora Latreille, lend themselves to such difficulties. This study employs environmental niche mapping (ENM) and traditional morphological analyses to investigate the validity of the subjective synonymy of Anthophora (Heliophila) curta Provancher with the senior synonym A. squammulosa Dours. Eleven of fifty morphological characters consistently differentiate the two putative species, with an additional five characters sometimes separating them. Additionally, based on over 1000 georeferenced museum specimens, the geographic ranges of the two taxa do not overlap. The two entities also react differently to the bioclimatic variables based on correlation analysis. We further tested the two-species hypothesis by constructing ENMs with informative bioclimatic variables associated with locality records. Their modelled distributions overlapped less than 1%, suggesting discrete environmental boundaries. The variables which contributed most to each species’ model also differed. These differences are explored in relation to their habitats. The combined morphological and biogeographic analysis indicates that A. curta and A. squammulosa are distinct species. Based on the accumulated evidence the synonymy is formally rejected and A. curta is recognized as a valid species. Five additional taxa (A. bispinosa Cockerell, A. franciscana Cockerell, A. usticauda Cockerell, A. u. cinerior Cockerell, A. zamoranella Cockerell) are newly synonymized with A. squammulosa and Anthophora curta var. melanops Cockerell is newly synonymized with A. curta. Implications outside of taxonomy are discussed.